PENGARUH NEPOTISME TERHADAP KEHENINGAN, KETERASINGAN DAN KOMITMEN ORGANISASIONAL PADA KARYAWAN PERUSAHAAN PERKEBUNAN SWASTA - Ricca Hendarti, Lenny Rakhmawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This research aims to determine the effect of nepotism on organizational silence, alienation and organizational commitment. The sample used in this study were employees working at PT. Nusa Pusaka Kencana. This research method using questionnaire as a research instrument. Questionnaires were successfully analyzed 120 questionnaires. Probability sampling system had been used for sampling technique because the profitability of the elements in the population to be selected as the sample is known, and the type used is total sampling. Simple Linear Regression is used as a method of analysis to determine the effect of the variables involved. The results showed that the independent variable nepotism show the positive influence and significant (sig 0.05) on organizational silence, alienation and organizational commitment. Key Word: Organizational Silence, Alienation and Organizational Commitment.